The First World War and its aftermath : the shaping of the Middle East - Fraser, T. G. (Gingko Library, 2015)
"This book gathers together leading scholars in the field to examine the impact of the First World War on the Middle East, so crucial to understanding the conflicts unfolding in the region today. In addition to recounting the international politics of the Great Powers that drew lines in the sand, contributors address topics ranging from the war's effects on women, the experience of the Kurds, sectarianism, the evolution of Islamism, and the importance of prominent intellectuals like Ziya Gökalp and Michel 'Aflaq. They examine the dissolution of the Ottoman Empire, the exploitation of notions of Islamic unity and Pan-Arabism, the influences of Wilson and American ideals on Middle East leaders, and likewise the influence of Lenin's vision of a communist utopia. Altogether, they tell a story of promises made and promises broken, of the struggle between self-determination and international recognition."--Provided by publisher.